Brand perceptions among school children - Wan Rashid, Wan Edura; Omar, Azura; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
This paper aims to explore the perception of children towards brand consciousness by using drawings and open-ended questions. A total of 20 primary school were requested to draw what they think about two statements given related to a person with branded materials and a person without branded materials. After drawing, respondents were personally interviewed regarding belongings of branded goods with cheerfulness, friendship, behaviour characters and desire for belongings. Results from the analysis of the drawings and interviews indicate that that there are significant differences in the children perception of someone with or without branded materials. Based on these findings, one hypothesis was proposed about perception of children with regard the knowledge of brand awareness.